Multiagent System With Periodic and Event-Triggered Communications for Solving Distributed Resource Allocation Problem - Li, Kaixuan; Liu, Qingshan; Zeng, Zhigang (IEEE transactions on systems, man, and cybernetics. Systems, 2023)
This article mainly investigates how to reduce the communication cost in multiagent system (MAS) for distributed optimization. First, a continuous-time distributed optimization model based on MAS is proposed for resource allocation (RA) with periodic communication. All agents in the system do not need to be in constant contact with their neighbors, but contact at set intervals. This will greatly reduce the communication consumption of the system. Second, to further reduce the communication cost, MAS with event-triggered communication is proposed based on periodic communication. It is proved that the system is convergent to an optimal solution of the investigated problem subject to bound and equality constraints. Finally, two examples with simulations are given to verify the performance of the proposed system.